Outcomes after chronic total occlusion percutaneous coronary interventions: an observational study of 5496 patients from the Pan-London CTO Cohort. Issue 7 (November 2018) - Jones, Daniel A.; Rathod, Krishnaraj S.; Pavlidis, Antonis N.; Gallagher, Sean M.; Astroulakis, Zoe; Lim, Pitt; Sirker, Alexander; Knight, Charles J.; Dalby, Miles C.; Malik, Iqbal S.; Mathur, Anthony; Rakhit, Roby; et al.
Abstract : Background: Chronic total occlusions (CTO) are commonly encountered in patients undergoing coronary angiography; however, percutaneous coronary intervention (PCI) is infrequently performed owing to technical difficulty, the perceived risk of complications and a lack of randomized data. The aim of this study was to analyse the frequency and outcomes of CTO-PCI procedures in a large contemporary cohort of successive patients. Patients and methods: We undertook an observational cohort study of 48 234 patients with stable angina of which 5496 (11.4%) procedures were performed for CTOs between 2005 and 2015 at nine tertiary cardiac centres across London, UK. Outcome was assessed by in-hospital major adverse cardiac events and all-cause mortality at a median follow-up of 4.8 years (interquartile range: 2.2–6.4 years). Results: Over time, there was an increase in the proportion of elective PCI procedures performed for CTOs, but no increase in the absolute number. Overall success rates increased over time (74.3% in 2005 to 81.5% in 2015; P =0.0003) despite an increase in case complexity (previous myocardial infarction, diabetes, renal failure, previous coronary artery bypass grafting, peripheral vascular disease and left ventricular impairment) that correlated with procedural advancements. Successful CTO PCI was associated with lower mortality [9.5%, 95% confidence interval (CI): 8.1–11.6 vs. 15.3%, 95% CI: 13.7–20.6, P <0.0001] that persisted after multivariate cox analysis (hazard ratio: 0.37, 95% CI: 0.25–0.62) and propensity matching (hazard ratio=0.36, 95% CI: 0.18–0.73, P =0.0005). Conclusion: Successful procedures were associated with lower mortality suggesting that the greater uptake of CTO PCI may improve clinical outcomes in a wider population than are currently being offered therapy. Abstract : Supplemental Digital Content is available in the text.